Systematic review of the fear of crime: An Ibero-Latin American Perspectives of the Concept - Reyes-Sosa, Hiram (2025)
In academic literature, there is a lack of agreement on the conceptualization of fear of crime. Thus, some research proposes that this construct should be measured unidimensionality. Other research defends the idea that fear of crime should be categorized in multidimensional terms. The aim of this study is to propose a systematic review of the construct of fear of crime in Ibero-Latin American with the objective of identifying its conceptualizations and associated variables. Using the PRISMA (Preferred Reporting Items for Systematic Review) methodology, articles published in Spanish were searched in the following databases: Scielo (n = 194), Redalyc (n = 270), Latindex (n = 5) y Dialnet (n = 176). The evidence found in the articles demonstrates that in the case of Ibero-Latin American, there is ambiguity in the construct, as fear of crime is often referred to as a concept equivalent to, for example, the perception of insecurity. Furthermore, it appears that fear of crime is conceptualized largely from an emotional perspective. Finally, the variables most studied in research on fear of crime are those related to its individual-psychological effects (well-being or emotions) and victimization (direct and indirect).